2010
DOI: 10.1002/cjoc.201090110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Adsorption Performance of Surface‐Grafted Co(II)‐Imprinted Polymer for Selective Removal of Cobalt

Abstract: The surface-grafting ion-imprinting technology was applied to synthesis of a new Co(II)-imprinted polymer [Co(II)-IP], which could be used for selective removal of Co(II) from aqueous solutions. The prepared polymer was characterized by using the infrared spectra (IR), X-ray diffractometer (XRD), X-ray energy dispersion spectroscopy (EDS) and scanning electron microscopy (SEM). The maximum adsorption capacity values for the Co(II)-imprinted polymer and non-imprinted polymer (NIP) were 22 and 8 mg/g, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…By exploring the influence of the height of the adsorption column, [ 32 ] solution flow rate, and the initial concentration on the dynamic adsorption of As(V), the penetration point was set as the time when C t / C 0 = 0.1 and the depletion point as the time when C t / C 0 = 0.9 (Figure 3). Our study revealed that the higher the height of the adsorption column, the higher the time taken for the breakthrough point and depletion point to be reached.…”
Section: Resultsmentioning
confidence: 99%
“…By exploring the influence of the height of the adsorption column, [ 32 ] solution flow rate, and the initial concentration on the dynamic adsorption of As(V), the penetration point was set as the time when C t / C 0 = 0.1 and the depletion point as the time when C t / C 0 = 0.9 (Figure 3). Our study revealed that the higher the height of the adsorption column, the higher the time taken for the breakthrough point and depletion point to be reached.…”
Section: Resultsmentioning
confidence: 99%
“…The value of present work was lower than that of our previous studies (300 min). 18 With changing the concentrations of the solution from 3.0 to 8.0 mg/L, the absolute amount of Co(II) ions per unit of adsorbent increased from 2.55 to 8.50 mg/g at 25 ℃.…”
Section: Effect Of Contact Time At Different Initial Ion Concentratiomentioning
confidence: 96%
“…Exposure to t isotopes causes hair loss, skin burns, anemia, and cancer [149]. Recently, IIPs have ga significant interest in removing Co²⁺ ions due to their selectivity and recognition ab The use of inorganic materials (such as palygorskite, titanate whiskers, SBA-15) gra on chitosan or polyethyleneimine, which have been crosslinked with epoxy functiona organic or silane coupling agents, for the Co-IIPs preparation, are explored in var studies [150][151][152][153]. Figure 12 presents a method used for the synthesis of IIPs from chito [154], copyright 2012, Mishad et al…”
Section: Cobaltmentioning
confidence: 99%